The Effect of Integrity, Independence, Competence, Work Experience and Work Pressure on Audit Quality: Empirical Study at the Inspectorate of Pandeglang Regency - Rohaelis Nuraisiah; Anggi Haerani; Edward Fazri (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of integrity, independence, competence, work experience, and work pressure on audit quality at the Inspectorate of Pandeglang Regency. The data used in this research is direct questionnaire data distributed to 51 samples of respondents by purposive sampling. The analytical method used in this research is multiple linear regression analysis using SPSS v23. The variable used as the dependent variable is audit quality. Meanwhile, the variables used as independent variables are integrity, independence, competence, work experience, and work pressure. The results of this study indicate that partial integrity and independence do not affect audit quality. While competence, work experience, and work pressure affect audit quality. Simultaneously, integrity, independence, competence, work experience, and work pressure affect audit quality at the Inspectorate of Pandeglang Regency